STORYBOARD ANIMATIC SEBAGAI MEDIA PEMBELAJARAN DENGAN MOTION GRAPHIC STUDI KASUS ANIMASI 4MPERA - Anggara, Obik Dwi; Amin, Miftakul; Ema Laila (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
In animation courses, the animatic storyboard stage is very important. However, it is often overlooked in learning so that students consider it not too important in animation production. In fact, this stage is very important in the animation industry because it is a reference in producing animation. Therefore, many students in the Digital Multimedia Informatics Technology Study Program do not understand about animatic storyboards. From the tests carried out as observations, 12 respondents who were students majoring in Computer Engineering, Digital Multimedia Informatics Technology Study Program, 10 of them did not know how to make an animatic storyboard. The design of motion graphic videos as learning media aims to increase awareness and educational media for students